STARTEGI PEMASARAN BERBASIS ONLINE USAHA SALAK BUAH KHAS KAMPUNG BANJAR SEMINAI KECAMATAN DAYUN KABUPATEN SIAK: STARTEGI PEMASARAN BERBASIS ONLINE USAHA SALAK BUAH KHAS KAMPUNG BANJAR SEMINAI KECAMATAN DAYUN KABUPATEN SIAK - Firdaus, Emilda; Mubarak, Mubarak; Andrikasmi, Sukamarriko; Fitriansyah, Aidil; Rozi, Fahrur (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Banjar Seminai Village, Dayun Subdistrict, Siak District, Riau Province, is known as a production center for its distinctive honey salak. Although the salak business in this area has grown rapidly, farmers face challenges in marketing their products, especially in finding direct buyers. This service aims to analyze the factors that influence the marketing strategy of honey salak and explore alternative effective online-based marketing strategies. Using survey methods and statistical analysis, this service evaluates the extent to which the application of digital platforms can increase sales and consumer satisfaction. It is hoped that the results of this service can provide insights and practical recommendations for business actors and policy makers to optimize the use of digital technology, so that the salak business in Banjar Seminai Village can continue to grow and provide benefits to the local community. The success of adaptive and innovative marketing strategies is expected to increase the competitiveness and sustainability of agricultural businesses in the area.